A leadership development programme for agricultural entrepreneurs in Sweden. Issue 4 (8th August 2018) - Ulvenblad, Pia; Cederholm Björklund, Jennie
ABSTRACT: Purpose : This article describes the five-phase process of a leadership development programme conducted with agricultural entrepreneurs who own and manage dairy farms in Sweden. The programme primarily focused on leadership of employees and on self-leadership. The article's purpose is to present a template for leadership development programmes that can be used in the agricultural sector and in other industry sectors as well. Design/Methodology : The empirical data come from interviews with agricultural entrepreneurs, agricultural advisors and authors of a book on leadership in its various forms. Observations were also conducted of the instruction in the leadership development programme. Findings : First, agricultural entrepreneurs (and possibly entrepreneurs in other sectors) benefit from leadership development programmes in which the concept and practice of self-leadership are emphasized. Second, such programmes are more valuable to participants if other actors (e.g. academics and advisors) are participants. Third, coaches are useful as support for the programmes' participants. Practical Implications : An implication of this study is the finding that working with the knowledge transfer and dissemination to advisors and entrepreneurs in the agricultural sector can enhance leadership competences in the industry. Role transformation (e.g. advisor to coach) can also enhance the transfer of such leadership competences. Theoretical implications : An implication for theory is to include a self-leadership module in leadership theories about learning leadership in development programmes. Originality/Value : Knowledge transfer and dissemination through leadership development programmes for agricultural advisors and entrepreneurs can have a beneficial effect on industry leadership and management. In addition to the traditional leadership skills that many leadership development programmes teach, such programmes also need to emphasize self-leadership.